2021
DOI: 10.48550/arxiv.2112.05344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleeping Model: Local and Dynamic Algorithms

Abstract: The distributed setting represents a communication network where each node is a processor with its own memory, and each edge is a direct communication line between two nodes. Algorithms are usually measured by the number of synchronized communication rounds required until the algorithm terminates in all the nodes of the input graph. In this work we refer to this as the clock round complexity. The setting is studied under several models, more known among them are the LOCAL model and the CON GEST model. In recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…They showed that problems in this class admit a deterministic algorithm that runs in 𝑂 (log Δ) awake time and 𝑂 (Δ 2 ) round complexity. Maimon [34] presents trade-offs between awake and round complexity for O-LOCAL problems.…”
Section: Related Work and Comparisonmentioning
confidence: 99%
“…They showed that problems in this class admit a deterministic algorithm that runs in 𝑂 (log Δ) awake time and 𝑂 (Δ 2 ) round complexity. Maimon [34] presents trade-offs between awake and round complexity for O-LOCAL problems.…”
Section: Related Work and Comparisonmentioning
confidence: 99%
“…They also define the class of O-LOCAL problems (that includes MIS and coloring) and showed that problems in this class admit a deterministic algorithm that runs in O(log ∆) awake time and O(∆ 2 ) round complexity. Maimon [28] presents trade-offs between awake and round complexity for O-LOCAL problems.…”
Section: Related Workmentioning
confidence: 99%